Synthesis and photovoltaic properties of 4, 9-dithien-2′-yl-2, 1, 3-naphthothiadiazole-based D-A copolymers. (19th November 2015) - Shen, Ping; Bin, Haijun; Chen, Lixia; Zhang, Zhi-Guo; Li, Yongfang
Abstract: A series of donor-acceptor (D-A) conjugated copolymers (PBDTNT, PCDTNT, PFDTNT, andPNDTNT ) based on a new acceptor unit of 4, 9-dithien-2′-yl-2, 1, 3-naphthothiadiazole (DTNT) and different donor unit of benzodithiophene, carbazole, fluorene, or naphthalene, were synthesized and characterized as donor in polymer solar cells (PSCs). The effect of different donor units on the physicochemical properties of the polymers was investigated systematically. The copolymers showed relatively low-lying HOMO energy levels of around −5.45 eV, which is favorable for achieving high open-circuit voltage ( V oc ). The photovoltaic properties of these copolymers were studied by fabricating the PSCs with the polymer as donor and PC70 BM as acceptor. PSCs based onPBDTNT :PC70 BM (1:4, w/w) exhibited a power conversion efficiency (PCE) of 2.73%, a high V oc of 0.90 V, a short-circuit current density ( J sc ) of 9.45 mA cm −2, and a fill factor of 32.1% via optimizing the device fabrication conditions, including the polymer/PC70 BM blend ratio, solvent additive and treatment with methanol. With the same fabrication method, PSCs based onPCDTNT, PFDTNT, andPNDTNT showed PCEs of 2.26, 1.57 and 1.45%, and high V oc values of 0.90, 0.92 and 0.92 V, respectively. Graphical abstract: A series of donor-acceptor (D-A) conjugated copolymers (PBDTNT, PCDTNT, PFDTNT, andPNDTNT ) based on a new acceptor unit of 4, 9-dithien-2′-yl-2, 1, 3-naphthothiadiazole (DTNT) and different donor unit of benzodithiophene, carbazole, fluorene, or naphthalene, were synthesized and characterized as donor in polymer solar cells (PSCs). The effect of different donor units on the physicochemical properties of the polymers was investigated systematically. The PSCs based onPBDTNT /PC70 BM gave a PCE of 2.73%, with a high V oc of 0.90 V. Highlights: 4, 9-Dithien-2′-yl-2, 1, 3-naphthothiadiazole was used as an effective acceptor unit for high V oc polymer solar cells. Optoelectronic properties ofDTNT -based polymers can be tuned by copolymerizing with different donor units. Polymer solar cells based onPBDTNT exhibited a PCE of 2.73% with a V oc of 0.90 V.